2020
DOI: 10.1371/journal.pone.0228317
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus genotyping of Giardia duodenalis in Southwestern Iran. A community survey

Abstract: Giardia duodenalis is one of the main enteric pathogens associated with diarrheal disease. In developing countries, giardiasis is a major public health concern, particularly in children under five years of age. This study aimed to evaluate the occurrence and genetic diversity of G. duodenalis causing human infections in Shushtar County, Southwestern Iran. Individual faecal specimens were collected from 1,163 individuals (male/female ratio: 0.9; age range 2-75 years) with (n = 258) and without (n = 905) gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Giardia duodenalis genotyping at the sub-assemblage level allowed us to better identify zoonotic isolates and to define the potential risk of zoonotic transmission in the study area. Previous data showed that AII sub-Assemblage is predominantly found in humans, thus considered zoonotic (Ballweber et al, 2010;Cacciò et al, 2002;Skhal et al, 2017;Sprong et al, 2009), whereas while AIII has been detected in humans only occasionally, also in Italy (Cacciò et al, 2002), infecting preferentially wild hoofed animals (De Liberato et al, 2015;Rafiei et al, 2020;Sprong et al, 2009) and sometimes cats (Lebbad et al, 2010). In our data, a potential risk of zoonotic transmission could be deduced from the clusters obtained in the phylogenetic analysis, which grouped human and cat isolates TA B L E 1 Descriptive analysis and association between direct immunofluorescence assay outcome for Giardia duodenalis and individual and colony variables in cats from central Italy Abbreviation: SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Giardia duodenalis genotyping at the sub-assemblage level allowed us to better identify zoonotic isolates and to define the potential risk of zoonotic transmission in the study area. Previous data showed that AII sub-Assemblage is predominantly found in humans, thus considered zoonotic (Ballweber et al, 2010;Cacciò et al, 2002;Skhal et al, 2017;Sprong et al, 2009), whereas while AIII has been detected in humans only occasionally, also in Italy (Cacciò et al, 2002), infecting preferentially wild hoofed animals (De Liberato et al, 2015;Rafiei et al, 2020;Sprong et al, 2009) and sometimes cats (Lebbad et al, 2010). In our data, a potential risk of zoonotic transmission could be deduced from the clusters obtained in the phylogenetic analysis, which grouped human and cat isolates TA B L E 1 Descriptive analysis and association between direct immunofluorescence assay outcome for Giardia duodenalis and individual and colony variables in cats from central Italy Abbreviation: SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Our sequence data revealed that assemblage A was more prevalent than assemblage B (53.3 vs 43.3%) in the clinical population investigated. Similar assemblage frequencies have been documented in neighbouring Iran (Hooshyar et al ., 2017; Kasaei et al ., 2018; Rafiei et al ., 2020). These results are in sharp contrast with the European scenario, where assemblage B is the predominant assemblage reported in most countries (Feng and Xiao, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Giardia lamblia and Giardia duodenalis) is a protozoan intestinal parasite, which can infect various mammalian hosts, including humans, wildlife, livestock, and companion animals. 2 The prevalence of Giardia infection varies from approximately 2-5% in the industrialized world 3 to 20-30% in low-and middle-income countries, 4,5 with children typically being more frequently infected than adults. 6 Owing to the elevated burden of G. intestinalis-related illnesses in developing countries, its impact on developmental and socioeconomic improvements, and its close connection with poverty, this parasite has been included in the WHO's Neglected Diseases Initiative since 2004.…”
Section: Introductionmentioning
confidence: 99%